First record of the genus Nedinoschiza Cameron (Hymenoptera: Braconidae) from the Indian subcontinent with the description of a new species from the Western Ghats - Ranjith, A.p.; Priyadarsanan, Dharma Rajan (Zootaxa, 2021)
The Indo-Australian braconine genus, Nedinoschiza Cameron, 1911 is reported for the first time from the Indian subcontinent. A new species, N. indica Ranjith sp. nov. is described and illustrated with the taxonomic key for the extant Nedinoschiza species. The generic diagnosis of Nedinoschiza is revised along with the illustrations of two species viz., N. seminigra (Szépligeti) and N. pinguis Papp.